PERLINDUNGAN HUKUM TERHADAP NASABAH BANK PADA PENARIKAN TABUNGAN NASABAH OLEH PIHAK LAIN BERDASARKAN PRINSIP KEHATI-HATIAN DALAM PERBANKAN (STUDI DI PT. BANK RIAU KEPRI BUTIK MALL SKA PEKANBARU) - Sinulingga, Andi Sanjaya; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Banking institution is one of institution which has an important strategic role in Indonesian development. In conducting its business activities, it must perform the duties and authorities carefully, thoroughly and professionally in order to gain public’s trusty. In Article 2 of banking law told that the activity of banking is guided by some principles or basis, namely economic democracy principle and the precautionary principle. This study examines the issues relating to the legal protection of the customer on the withdrawal of savings by the other party based on the precautionary principle in banking that occurs in PT. Bank Riau Riau Islands Boutique Mall SKA Pekanbaru. The aim of the study is to determine the legal protection of customers in the withdrawal of savings by other parties and determine the banking’s responsibility of the customer for withdrawal of saving by other parties.The study was conducted by using Juridical Sociological Research. The source of the data was obtained from primary data and secondary data, then for the technic of collecting the data was obtained by using interview and literature. Furthermore, the researcher also used qualitative analysis, an analysis of the data are clearly described in the form of sentences in order to obtain the clear image after that the conclusion can be gotten inductively.From the result of the study can be concluded that the legal protection of customer related to withdrawal of saving by other parties are: customer get protection by the bank in the form of good response to customer. The customer get the good response was in the form of in providing information, letting the customer give complaints and also collecting evidences. Then, the responsibility of the bank to customer related withdrawal of savings by the other party was the teller negligence in running their duties which resulted in loss of customer. For the case, the bank need to responsible for providing compensation to the client, but the first thing that should be done was proofing the truth about client indemnity that it was really the fault of the bank, further the replacement should be delegated to the teller who did negligence. This study suggests that all of bank staff should be more cautious, careful and meticulous in operating all the desk jobs, and the researcher expected that bank must have specific regulations which regulate transaction about the withdrawal of saving by other parties.Keywords: Bank, Customer Protection, Responsibility